Genome-wide analysis of LysM gene family members and their expression in response to Colletotrichum fructicola infection in Octoploid strawberry(Fragaria × ananassa) - Zhang, Liqing; Li, Shuigen; Fang, Xianping; An, Haishan; Zhang, Xueying (Frontiers in Plant Science, 2023)
The cultivated octoploid strawberry (Fragaria × ananassa) is an economically important fruit that is grown worldwide. The lysin motif (LysM) protein family is composed of the major class of plant pattern recognition receptors, which play important roles in sensing pathogen-associated molecular patterns (PAMPs), and subsequently triggers downstream plant immunity. In the present study, a comprehensive, genome-wide analysis of F. × ananassa LysM (FaLysM) genes was performed to investigate gene structures, phylogenic relationships, chromosome location, collinear relationships, transcription factor binding sites, and protein model analysis. We aimed to identify the LysM genes involved in the defense against plant pathogens. A total of 14 FaLysM genes were identified in the F. × ananassa genome and divided into 2 subgroups (LYP and LYK) on the basis of the phylogenetic analysis. The Ka/Ks ratio for the duplicated pair of most FaLysM genes was less than 1, which indicates that the selection pressure was mostly subject to the purifying selection during evolution. The protein model analysis revealed that FaLysM2-10 contain conserved mode of chitin binding, which suggest the potential role of FaLysM2-10 in pathogen perception and plant immunity. The RNA-Seq results showed the differential regulation of 14 FaLysM genes in response to Colletotrichum fructicola infection, implying the complex interaction between C. fructicola and strawberry. Knockout of candidate effector gene CfLysM2, which was previously proved to be highly expressed during C. fructicola infection, resulted in the up-regulation of six FaLysM genes (FaLysM1, FaLysM2, FaLysM3, FaLysM7, FaLysM8, and FaLysM12), indicating the competitive relationship between CfLysM2 and FaLysM genes. Overall, this study provides fundamental information on the roles of LysM proteins in octoploid strawberry and its interaction with C. fructicola, laying useful information for further investigation on the C. fructicola-strawberry interaction and strawberry resistance breeding.